Barriers and facilitators to mobility of patients hospitalised on an acute medical ward: a systematic review. (6th July 2022) - Mani, Hugo; Möri, Charlotte; Mattmann, Martina; Liechti, Fabian; Inauen, Jennifer; Aujesky, Drahomir; Donzé, Jacques; Aubert, Carole E
Abstract: Background: low patient mobility is common during hospitalisation and is associated with adverse outcomes. To change practice, interventions should address barriers and facilitators to mobility. Our aim was to systematically review the literature to provide a synthesised overview of patient-, health care professional (HCP)- and environment-/system-related barriers and facilitators to mobility of patients hospitalised on an acute care medical ward. Methods: we searched Medline, Embase, PsycInfo, Web of Science Core Collection, Cochrane CENTRAL, CINHAHL and Google Scholar (inception to 18 October 2021) to identify studies reporting barriers and/or facilitators to mobility of adults hospitalised on an acute medical ward. We applied a deductive and inductive thematic analysis to classify barriers and facilitators into themes and subthemes relevant for clinical practice. Results: among 26 studies (16 qualitative, 7 quantitative and 3 mixed methods), barriers and facilitators were categorised into 10 themes: patient situation, knowledge, beliefs, experiences, intentions, emotions, social influences, role/identity, implementation/organisation and environment/resources. Barriers included patient characteristics (e.g. impaired cognitive/physical status) and symptoms, HCPs prioritising other tasks over mobility, HCPs labelling patients as 'too sick', fear of injury, lack of time, lack of clarity about responsibility, patient medical devices and non-encouraging environment. Facilitators included knowledge of mobility importance, HCP skills, interdisciplinarity, documentation and unit expectations, encouraging staff, goal individualisation, activity programme, family/visitor/volunteer support and availability of equipment. Conclusion: this synthesised overview of patient-, HCP- and environment-/system-related barriers and facilitators to mobility of adults hospitalised on an acute medical ward can help researchers and clinicians focus on what can realistically be influenced to improve mobility. Systematic review registration: PROSPERO, CRD42021285954.